Positive nikolsky sign and â€œpinpoint lake of pusâ€ in acute generalized exanthematous pustulosis: a case report - Ketut Alit Pinidha Savitri; Ketut Suteja Wibawa; Komang Harry Supradnyan (Intisari Sains Medis, 2020)
Introduction: Acute generalized exanthematous pustulosis (AGEP) is a severe, usually drug-related reaction, characterized by an acute onset of mainly small non-follicular pustules on an erythematous base and spontaneous resolution usually within two weeks. Current report aims to present management of AGEP in our center at Singaraja Regional Hospital, Bali-Indonesia.Case: A 78 years old woman with a history of acute coronary syndrome, was reported to have a severe allergic drug reaction. Patients reported taking cefixime medication for the past 2 days because of acute bronchitis. The patient was hospitalized because of the complaint, and diffuse miliary pustules were found above the base of erythematous skin. On examination of lesions, the Nikolsky sign was positive on lesions in the back and abdomen without any tenderness. Histopathological examination was suitable for the diagnosis of acute generalized exanthema pustulosis (AGEP). Systemic intravenous corticosteroid with oral antihistamines was choosen as a primary treatment for this patient.Conclusion: Treatment is based on the removal of the causative drug, supportive care, infection prevention and use of potent topical or systemic steroids